A Research-Infused Undergraduate Music Curriculum - Young, Gregory; Don, Gary W.; Rieck, Alan (Scholarship and practice of undergraduate research, 2017)
As music programs at colleges and universities join the undergraduate research movement, many faculty and administrators may be unsure of terminology, educational practices, or ways to combine some of the creative aspects of music degree requirements into compelling undergraduate research projects. One of the biggest challenges is embedding undergraduate research and creative activity (URSCA) into the curriculum so that more students experience it without placing additional burdens on faculty. This article offers examples within the music degree and general education requirements at two universities that might serve as models. They range from freshman year to senior capstone projects, offering students inspiring and active learning experiences that will enhance their engagement with the subject matter and link their learning with the discovery of knowledge and art.